Social Context, Stress, Neuropsychiatric Disorders, and the Vasopressin 1b Receptor - Caldwell, Heather K.; Aulino, Elizabeth A.; Rodriguez, Karla M.; Witchey, Shannah K.; Yaw, Alexandra M. (Frontiers in Neuroscience, 2017)
The arginine vasopressin 1b receptor (Avpr1b) is involved in the modulation of a variety of behaviors and is an important part of the mammalian hormonal stress axis. The Avpr1b is prominent in hippocampal CA2 pyramidal cells and in the anterior pituitary corticotrophs. Decades of research on this receptor has demonstrated its importance to the modulation of social recognition memory, social forms of aggression, and modulation of the hypothalamic-pituitary-adrenal axis, particularly under conditions of acute stress. Further, work in humans suggests that the Avpr1b may play a role in human neuropsychiatric disorders and its modulation may have therapeutic potential. This paper reviews what is known about the role of the Avpr1b in the context of social behaviors, the stress axis, and human neuropsychiatric disorders. Further, possible mechanisms for how Avpr1b activation within the hippocampus vs. Avpr1b activation within anterior pituitary may interact with one another to affect behavioral output are proposed.